Violations of International Code of Breast‐milk Substitutes (BMS) in commercial settings and media in Bangladesh - Sifat P. Sheikh; Syeda M. Akter; Faugia I. Anne; Santhia Ireen; Jessica Escobar‐Alegria; Kirsten Kappos; Deborah Ash; Sabrina Rasheed (Maternal and Child Nutrition, 2022)
Abstract The International Code of Marketing of Breast‐milk Substitutes (BMS) instituted to protect breastfeeding against unethical marketing, has been adopted by many countries, including Bangladesh. Despite national adoption, evidence suggests violations occur and inadequate BMS Code implementation is an issue. The study aimed to assess violations of the International BMS Code and the national ‘Breast‐milk Substitutes, Infant Foods, Commercially Manufactured Complementary Foods and the Accessories Thereof (Regulation of Marketing) Act, 2013’ of Bangladesh in commercial settings (retail outlets and media) in Bangladesh, for different types of milk, bottles, and teats using a standardized Network for Global Monitoring and Support for Implementation of the Code and Subsequent relevant World Health Assembly Resolutions (NetCode) protocol. This cross‐sectional quantitative study was conducted in Bangladesh from January to September 2018 in Dhaka, Chattogram, and Sylhet cities. Descriptive statistics were reported and χ2 tests were conducted to assess differences between categorical variables of interest. Data were analysed using SPSS version 20. In retail outlets, there were higher proportion of violations observed in Dhaka than in Sylhet and Chattogram (p < 0.001). Significantly greater proportion of violations in product labels occurred among products sold without local distributors compared to others (p < 0.05); violations were higher among “other milk” for children aged 0 to <36 months compared to formulas and growing‐up milk (p < 0.05). Among media channels, internet clips had significantly higher proportions of violations compared to television, radio and newspaper (p < 0.001). BMS Code violations were prevalent in product labels and promotion of products through retail outlets. The study findings highlight the need for specific multisectoral strategies for better enforcement of BMS Code and points to the need for periodic assessment of Code violations.